Revisiting Greek lighthouses: A new perspective in cultural tourism - Kakaroucha Paraskevi (University Educons, Faculty of Sports and Tourism, Novi Sad, 2021)
Greece owns one of the most extensive and best organized coastal and open sea lighting systems across the world. Some of the most breathtaking and historic lighthouses and beacons of the Hellenic Lighthouse Network have been characterized as "Monuments of Modern Cultural Heritage" and are available to visitors under certain circumstances. Greek lighthouses are austere albeit multi symbolic structures that enchant people seeking refined and reclusive experiences beyond the mass tourism spectrum. This paper aims at succinctly presenting the history of Greek lighthouses and examining the perspective of their valorization in cultural tourism, taking into account their legal framework, ownership status and inherent worthiness. Lighthouses represent tangible and intangible cultural values, which deserve to be rediscovered and communicated in ways that ensure sustainability and protection for lighthouse buildings and surrounding areas.